Permanent neonatal diabetes: combining sulphonylureas with insulin may be an effective treatment - Misra, S; Vedovato, N; Cliff, E; De Franco, E; Hattersley, A; Ashcroft, F; Oliver, N (Wiley, 2018)
Background: Permanent neonatal diabetes caused by mutations in the KCNJ11 gene may be managed with high‐dose sulfonylureas. Complete transfer to sulfonylureas is not successful in all cases and can result in insulin monotherapy. In such cases, the outcomes of combining sulfonylureas with insulin have not been fully explored. We present the case of a woman with diabetes due to a KCNJ11 mutation, in whom combination therapy led to clinically meaningful improvements. Case: A 22‐year‐old woman was found to have a KCNJ11 mutation (G334V) following diagnosis with diabetes at 3 weeks. She was treated with insulin‐pump therapy, had hypoglycaemia unawareness and suboptimal glycaemic control. We assessed the in vitro response of the mutant channel to tolbutamide in Xenopus oocytes and undertook sulfonylurea dose‐titration with C‐peptide assessment and continuous glucose monitoring. In vitro studies predicted the G334V mutation would be sensitive to sulfonylurea therapy [91 ± 2% block (n = 6) with 0.5 mM tolbutamide]. C‐peptide increased following a glibenclamide test dose (from 5 to 410 pmol/l). Glibenclamide dose‐titration was undertaken: a lower glibenclamide dose did not reduce blood glucose levels, but at 1.2 mg/kg/day insulin delivery was reduced to 0.1 units/h. However, when insulin was stopped, hyperglycaemia ensued. Glibenclamide was further increased (2 mg/kg/day), but once‐daily long‐acting insulin was still required to maintain glycaemia. This resulted in improved HbA1c of 52 mmol/mol (6.9%), restoration of hypoglycaemia awareness and reduced glycaemic variability. Conclusion: In people with KCNJ11 mutations causing permanent neonatal diabetes, and where complete transfer is not possible, consideration should be given to dual insulin and sulfonylurea therapy.